Development of a Physics Assessment Instrument to Measure High School Students Multirepresentation Skills in Momentum and Impulse - Khotimah, Khusnul; Fariyani, Qisthi (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2025)
This research is a Research and Development. Developed a multirepresentation test instrument to measure the multirepresentation skills of class XI students specializing in physics at SMA Negeri 1 Semarang on momentum and impulse. This was done because the multirepresentation skills of SMA Negeri 1 Semarang students had not been measured as a whole and maximally. The multirepresentation test instrument has been tested for suitability by experts and small-scale trials have been carried out on students. Based on the results of validity, reliability, level of difficulty and differentiability tests, 25 questions were obtained that were suitable for use in the field. The overall average percentage results of multirepresentation skills for class XI students specializing in physics at SMA Negeri 1 Semarang is in the good category with a percentage of 76.89%. Based on these results, the multirepresentation test instrument is suitable for use to measure students' multirepresentation skills as evidenced by students' multirepresentation skills being measured well to the instrument developed.